O ensino de leitura literária nas vozes de professores de português recém-formados - Almeida, Maria de Fátima Xavier da Anunciação de (2016)
The purpose of this study was to learn from graduates of the Faculty of Letters by listening to their voices of knowledge concerning the teaching of literary reading, carried out in basic education, in order to ascertain and understand which knowledge has been effectively apprehended by recent graduate teachers. A qualitative research approach has been used (LÜDKE e ANDRÉ, 1986) and on the background a case study (TRIVIÑOS, 2009) along with a critical discourse analysis (FAIRCLOUGH, 2001),specifically through referencial theorists of education (FREIRE, 2003; 2011; 2013) discourse (Fairclough, 2001), literature (CANDIDO, 1995; 1997), literary reading (ZILBERMAN, 1991; LAJOLO, 1994; 2001; LAJOLO and ZILBERMAN, 1996; BORDINI and AGUIAR, 1988; PAULINE, 2015 [2005]; COSSON, 2012) reader and literature through concepts of Aesthetics of Reception (ISER, 2002; JAUSS, 2002; LIMA, 2002; ZILBERMAN, 2008; BORDINI and AGUIAR, 1988; CHARTIER; BOURDIEU, 2011; ZILBERMAN and SILVA, 1999), who take into account these phenomena as social, historical, ideological and cultural practice. The discursive corpus was collected through semi-structured interviews conducted with graduates from the Faculty of Letters – class of 2013 from the Public University of Mato Grosso do Sul, Brazil. What justifies the study is the fact that it may contribute to assess the inicial pedagogical formation of Portuguese teachers in order to rethink policies for inicial pedagogical formation and also for readers formation across the country.The outcomes showed that mainly through intertextuality, the recent graduate Portuguese teachers bring in their voices the knowledge of the areas of linguitics, theory of literature and education that surpass the concepts of a traditional literature teaching. They also show that the teaching of literary reading should begin from the text, the literary work. The reader has an active role in the reading and the teacher is the mediator who suggests meanings to the literary text. Once they are now in the position of Portuguese teachers, and through the knowledge apprehended in the initial formation in the Faculty of Letters, the collaborators on this project could base their analysis. We were able to identify the impressions expressed in their speeches that brought in criticism to the teaching of literature while having their reading experience and practice grounded on the time they attended basic school.